Implementation of The Toddler Growth Stimulation Program During The Covid 19 Pandemic Period, Manggahang Village, Bandung Regency in 2020 - ria angelina marbun (Healthy-Mu Journal, 2022)
Growth and development at the age of toddlers can be a determinant of the success of a child's growth and development at a later stage. Research conducted by Soccoro, et al in the Philippines proved that there was an increase in psychosocial development by 6-11% in children aged 0-4 years who were stimulated for 2 years. Efforts to increase the prevention of growth and development deviations in children under five need to be checked regularly, namely in children less than 24 months it is done every 3 months according to schedule and children aged 24-72 months it is done every 6 months. This activity can be carried out several times in 1 month. The research objectives are study was to identify the schedule and implementation of the early detection program for child development during the COVID-19 pandemic in Bandung Regency. This type of research is descriptive non-analytic research with cross sectional quantitative method. Determination of the sample according to the sample criteria amounted to 43 mothers of children under five. Univariate analysis to determine the schedule for the implementation of the SDIDTK simulation at the age of 0-2 years, and ages 2-6 years, as well as the frequency distribution and to see the implementation variables of the simulation of early detection of growth and development of toddlers during the pandemic. The results showed that almost all 38 respondents (88%) supported the implementation of the detection of growth and development of toddlers, while only 5 (12%) did not support the implementation of the detection of growth and development of toddlers during the covid 19 pandemic. One of the efforts to prevent developmental disorders in infants and toddlers is to monitor growth and development even in the condition of the covid 19 pandemic in the area. Detection and simulation of child development is carried out routinely, not only for children with disorders but also for all toddlers every 6 months according to the age of the toddler. The research suggestion is that the puskesmas can monitor the implementation schedule for the detection of growth and development periodically with the help of health cadres. For educational institutions, it can be a reference for detecting growth and development of toddlers in lecture material and for further researchers, it is expected to be able to analyze factors related to the implementation of detection of growth and development in children in the condition of the covid 19 pandemic in the area.